Stability of yields of sorghum genotypes: Implications for animal production in the tropics - Osafo, E.L.K.; Owen, E.; Ellis, R.H.; Said, A.N.; Gill, M.; Sherington, J. (British Society of Animal Science, 1998)
The adoption of `improved' sorghum (Sorghum bicolor (L.) Moench) genotypes (i.e. drought tolerant, high grain-yielding and bird-resistant) by farmers in Ethiopia is low (Tilahun et al., 1992). Farmers prefer local, non-bird-resistant genotypes because their drought resistance and grain and stover yields are known (Osafo, 1993). Stover is important as both a livestock feed and fuel wood substitute in Ethiopia and elsewhere (Williams et al., 1997). Until recently (Kelley et al., 1991) sorghum breeders have focused mainly on drought tolerance, grain yield and bird-resistance, with no consideration being given to stover and its livestock-feeding value. The present study in Ethiopia evaluated traditional and improved genotypes of sorghum for environmental stability regarding yield of grain, yield of stover and stover feeding quality (leaf:stem ratio).